2014
DOI: 10.1097/jto.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Analyses from a Randomized, Placebo-Controlled, Phase IIIb Trial Comparing Bevacizumab with or without Erlotinib as Maintenance Therapy for the Treatment of Advanced Non-Small-Cell Lung Cancer (ATLAS)

Abstract: Patients with KRAS wild-type or EGFR mutation-positive NSCLC derived PFS benefits from B+E. However, EGFR IHC, EGFR FISH, and EGFR or KRAS mutation status were not strongly predictive of survival. A larger sample size would be needed to confirm the initial trends observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…1 and 2). AVAPERL [35,36] and ATLAS [37,38] were compared qualitatively with other maintenance trials, but not included in the NMA for efficacy analysis as they did not share a common comparator arm with the other included studies. Characteristics of included studies are provided in Table 1 with details in Appendix Tables A1-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2). AVAPERL [35,36] and ATLAS [37,38] were compared qualitatively with other maintenance trials, but not included in the NMA for efficacy analysis as they did not share a common comparator arm with the other included studies. Characteristics of included studies are provided in Table 1 with details in Appendix Tables A1-2.…”
Section: Resultsmentioning
confidence: 99%
“…[34] guidelines. a AVAPERL [35,36] and ATLAS [37,38] were not included in the network meta-analysis as there was no common comparator arm with other included maintenance trials.…”
Section: Performance Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that EGFR‐TKI combined with an antiangiogenic drug (bevacizumab) is effective in the treatment of advanced NSCLC, and can improve patient survival . The clinical study of bevacizumab combined with erlotinib in EGFR‐TKI resistance has also made breakthroughs.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have shown that EGFR-TKI combined with an antiangiogenic drug (bevacizumab) is effective in the treatment of advanced NSCLC, and can improve patient survival. [9][10][11][12] The clinical study of bevacizumab combined with erlotinib in EGFR-TKI resistance has also made breakthroughs. In the BELIEF study published at the 2015 European Cancer Congress, patients with advanced nonsquamous NSCLC and EGFR exon 19 deletion or exon 21 (L858R) mutation were enrolled.…”
Section: Introductionmentioning
confidence: 99%